Mud as a Construction Material in Rural Dwellings: Study of Thermal Performance in Composite Climate. - Dr. Janmejoy Gupta, Dr. Manjari Chakraborty, Sharon Mathew, Alankar Jharia (International Journal of Advanced Science and Technology, 2020)
Indoor thermal-comfort conditions can be improved by judicious selection of building materials. India has climatic conditions ranging from warm-humid to cold, with composite climate prevalent in considerably larger parts. Rural Indigenous mud-based architecture is a hitherto neglected aspect of architecture. Yet, 30% of the world’s total population lived in earthen structures in 2011. Mud huts are an intrinsic part of the culture and life of many rural-folk through generations. This paper deals with both the thermal properties and performance of mud in composite climatic regions in India. As a typical composite climatic region, Ranchi, the capital of the eastern Indian state of Jharkhand, has been considered. The primary thermal properties of mud, which determine its applicability and effective-use, have been studied with respect to the characteristics of composite climate. To design and build dwellings in composite climate region is toughest as they have varying climatic characteristics from season to season. This paper suggests a few measures to make existing mud dwellings a more climate-responsive option throughout the year in the composite climatic zones of the country.